Ignition Time for a Porous Medium Model with Low Thermal Conductivity - Ajadi, Suraju Olusegun (2014)
The ignition time for a porous medium combustion arising from a porous medium combustion model is considered. The effect of the activation energy parameter as well as the parameter which measures the ratio of oxygen consumption to that of the solid(fuel), on the ignition time is presented.